Kinderen zijn geboren kunstenaars : kunstenroute - een confrontatie. - Hoet, Jan; Poelman, Willy (Lichtervelde, 2001)
Desmet, An ; Van Laere, Catharina ; Tonnard, Philippe ; Lefever, Danny ; Missine, Geert ; Bober, Patrick ; Desplenter, Kurt ; Vankeirsbilck, Benny ; Bosschaert, Chris ; Wydooghe, Maarten ; Delameillieure, Elie ; Cornillie, Patrick ; Delrue, Ronny
Nederlands
Kinderen zijn geboren kunstenaars : kunstenroute. Lichtervelde. 5 en 6 mei 2001
boek